Challenges and Priorities for Quebec’s English-Language Education Continuum - Shoumarova, Lina (Quebec English-speaking Communities Research Network (QUESCREN), 2024)
This brief aims to inform the Standing Committee on Official Languages about challenges experienced in Quebec’s English-language minority education sector, and their impact on the education continuum from early childhood to post-secondary education and beyond. It summarizes findings from 11 research briefs on English-language education that QUESCREN produced and commissioned between 2021 and 2024. Additionally, it outlines priority areas for development in addressing these challenges.

Proposal for Including English-speaking Quebecers in the Programme d'accès a l'égalité en emploi (PAÉE) - Bourhis, Richard Y. (QUESCREN Lunch & Learn Series, 2024)

Network News - Quebec Community Groups Network (QCGN) (2024)

Innovative Mentorship Program Equips English-Speaking Quebecers With Workplace French Skills - Provincial Employment Roundtable (PERT) (2024)

PERT’s Recommendations Included in New Report on the Economic Development of Offi cial Language Minority Communities - Provincial Employment Roundtable (PERT) (2024)
Keywords: Official Language Minority Community (OLMC)

User Journeys of Language Learners Navigating Québec's French Language Training System - Provincial Employment Roundtable (PERT) (2024)
In recent years, the Québec government has significantly invested in French language training programs to promote greater usage of French in workplaces, schools, and society. Alongside these efforts, public discourse has emerged about the perceptions French-speaking Quebecers hold of English speakers, many of whom believe that English speakers are not committed to learning or using French despite the availability of publicly funded French language training resources. To explore these issues, this study examines the experiences, motivations, and barriers faced by English-speaking individuals in the labour force regarding French language training, particularly following the introduction of new services by Francisation Québec in June 2023. In doing so, we develop a broad typology of different language learners and explore their language-learning journey through interviews regarding their experiences and perceptions of the French language, language training, and navigating Québec’s labour market. We also interview subject matter experts to identify types of language learners and key themes. We then discuss the impact that these different experiences have on language learners’ outcomes, as well as the types of policy and program approaches that could improve their experiences with adult French language training programs.

New Report Calls for Coordinated Action to Tackle Employment Barriers Facing English Speakers in Capitale-Nationale - Provincial Employment Roundtable (PERT) (2024)

English Speakers in Gaspésie–Îles-de-la-Madeleine Experience the Highest Unemployment Rate in Québec, New Report Finds - Provincial Employment Roundtable (PERT) (2024)

English-speaking Quebec Plays Vital Role in Boosting French, Language Commissioner Says - Quebec Community Groups Network (QCGN) (2024)

English Speakers in the Laurentides Face Growing Economic Challenges, New Report Shows - Provincial Employment Roundtable (PERT) (2024)

Network News - Quebec Community Groups Network (QCGN) (2024)

New Language Directives in Health a Welcome, Significant Step, QCGN Says - Quebec Community Groups Network (QCGN) (2024)

English Speakers in Montérégie Facing Increased Unemployment and Ongoing Economic Disparities as Compared to Francophones - Provincial Employment Roundtable (PERT) (2024)

QCGN Pleased by Motion To Nix Identity Certificate for Health Care - Quebec Community Groups Network (QCGN) (2024)

Suicide Risk for Quebec’s English-speaking Population - Community Health and Social Services Network (CHSSN) (2024)

Health Directives Should Be Scrapped, Not Tweaked, QCGN Says - Quebec Community Groups Network (QCGN) (2024)

Income Disparities Between Quebec's English Speakers and Francophones Over Time - Donovan, Patrick; Bell, Shannon (Quebec English-Speaking Communities Research Network (QUESCREN), 2024)
This brief looks at income disparities between English speakers and Francophones in Quebec. It examines changes from the early 20th century, when Anglophones dominated many major industries, through political and cultural shifts between 1940 and 1980 to today’s landscape.

OQLF Has No Business in Quebec Operating Rooms, QCGN Says - Quebec Community Groups Network (QCGN) (2024)

New Census Data for Côte-Nord Shows No Improvement in the Economic Vitality of English Speakers Since 2016 - Provincial Employment Roundtable (PERT) (2024)

Building Bridges Between Communities Valuable, QCGN Annual Meeting Is Told - Quebec Community Groups Network (QCGN) (2024)

Attending the ACFAS Official Women Minority Language Communities Conference in Ottawa - Provincial Employment Roundtable (PERT) (2024)
Keywords: Official Language Minority Community (OLMC)

Challenges in Early Learning and Child Care for Quebec's English-speaking Community - Bell, Shannon (Quebec English-Speaking Communities Research Network (QUESCREN), 2024)
Early childhood education and care (ECEC). Early learning and child care. Nursery school. Preschool. Daycare. Centres de la petite enfance (CPE). There are many names and acronyms, but they all refer to the care and, ideally, educative care of young children in the years before compulsory elementary schooling. Modern wisdom views such programs as essential, and yet, in Quebec, English-speaking families face unique challenges in accessing them. This research brief explores these barriers, current efforts being made to address them, and potential solutions.

Demographic Decline of English Speakers in Certain Regions of Quebec - Bell, Shannon; Donovan, Patrick (Quebec English-Speaking Communities Research Network (QUESCREN), 2024)
How is English faring in Quebec? While 2021 census data reflect a recent increase in English usage in the Montreal and Gatineau areas, a more complex portrait emerges when examining other parts of Quebec and longer time periods. The 20th century was marked by a decline in the proportion of English speakers in most Quebec regions. The trend has shifted in the past 20 years, yet a notable decline continues in parts of coastal Quebec, the Eastern Townships, and Rouyn-Noranda. This brief looks at regions experiencing a decline in their English-speaking populations, and considers the forces driving recent changes.

Building Bridges : Perceptions and Realities About the English-speaking Communities of Quebec and their Relationship with French in Quebec and Bilingualism in Canada - Canada. Office of the Commissioner of Official Languages (2024)
The Office of the Commissioner of Official Languages (the Office of the Commissioner) has observed that, in recent years, the English-speaking communities of Quebec (ESCQ) have been the focus of much public discourse and debate in the province. Survey and census data indicate that, overall, the ESCQ are highly bilingual and value Canada’s broader linguistic duality, including the French language. The extent to which the general population is aware of these facets of the ESCQ is not clear, however, and the Office of the Commissioner wished to test the hypothesis that problematic myths may persist. In light of this context and with the modernization of the Official Languages Act by the federal government in 2023, which recognizes the need to “advance the existence of a majority-French society in a Quebec where the future of French is assured,” this research project is an opportunity to shed light on the relationship that the ESCQ have with the French language in Quebec and official bilingualism in Canada as a whole. This is also an opportunity to explore how Quebec’s English-speaking minority can be considered as bridge-builders or even as a potential ally of the promotion of French in Canada as a whole, with a view to developing a more constructive discourse that better acknowledges their contributions and, ultimately, deconstructs certain misperceptions.
Keywords: Official Language Minority Community (OLMC)

Resolution 2024-01 : French Instruction Availability - Quebec Federation of Home and School Associations (QFHSA) (2024)

Women in Official Language Minority Communities - Quebec English-speaking Communities Research Network (QUESCREN); Canadian Institute for Research on Linguistic Minorities (2024)
Keywords: Official Language Minority Community (OLMC)

Report Card on French May Bring More Coercive Measures, QCGN Says - Quebec Community Groups Network (QCGN) (2024)

Brief to the Standing Committee on Official Languages : The Importance of the University Research Ecosystem for Quebec’s English-Speaking Official Language Minority Community - O'Donnell, Lorraine (Quebec English-Speaking Communities Research Network (QUESCREN), 2024)
This brief calls for the Government of Canada to increase funding for research on Quebec’s English-speaking official language minority community (OLMC) and for the ecosystem in minority-language post-secondary institutions that is required for research production. The brief addresses the situation and needs, and proposes a solution.
Keywords: Official Language Minority Community (OLMC)

Portrait de l’évolution socioéconomique des Québécois et Québécoises d’expression anglaise - AppEco (Advisory Committee for English-speaking Quebecers (ACESQ), 2024)

English-language Health and Social Services Access in Québec : Comparison 2019-2023 - CROP (2024)

Socio-Demographic Profile of Québec's English-speaking Youth Aged 15-29 - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This report profiles the situation of English-speaking citizens of Québec who are engaged in the numerous transitions that are typically encountered between the ages of 15 and 29 in the critical passage from childhood to adulthood. Youth is a stage of life characterized by challenges that can be decisive in the quality of life of individuals and their communities and for most Québecers aged 15-29, these milestones are: completing school, gaining occupational experience and even starting a family and establishing a household. This report offers current information organized to support “the village” - from policymakers and program managers to public institutions, community organizations and networks - whose actions impact the lives of minority language youth striving to build their future and the future of all Québec’s citizens.

Network News - Quebec Community Groups Network (QCGN) (2024)

An Uphill Battle : Homelessness in Canada and Quebec and Its Likely Impact on the English-Speaking Community of Quebec - Quebec Community Groups Network (QCGN) (2024)
Keywords: Official Language Minority Community (OLMC)

Socio-Demographic Characteristics of Visible Minorities in Gatineau - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Gatineau, which is considered a territory equivalent to an MRC.

Socio-Demographic Characteristics of Visible Minorities in Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Laval, which is considered a territory equivalent to an MRC.

Socio-Demographic Characteristics of Visible Minorities in Longueil - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Longueil, which is considered a territory equivalent to an MRC.

Socio-Demographic Characteristics of Visible Minorities in MRC de L'Assomption - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de L'Assomption.

Socio-Demographic Characteristics of Visible Minorities in MRC de La Vallée-du-Richelieu - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de La Vallée-du-Richelieu.

Socio-Demographic Characteristics of Visible Minorities in MRC de Les Moulins - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de Les Moulins.

Socio-Demographic Characteristics of Visible Minorities in MRC de Roussillon - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de Roussillon.

Socio-Demographic Characteristics of Visible Minorities in MRC de Thérèse-De Blainville - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de Thérèse-De Blainville.

Socio-Demographic Characteristics of Visible Minorities in MRC de Vaudreuil-Soulanges - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de Vaudreuil-Soulanges.

Socio-Demographic Characteristics of Visible Minorities in Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Québec.

Socio-Demographic Characteristics of Visible Minorities in Québec City - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Québec City, which is considered a territory equivalent to an MRC.

Socio-Demographic Characteristics of Visible Minorities in Rest of Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for the rest of Québec.

Socio-Demographic Characteristics of Visible Minorities in RTS de Chaudière-Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de Chaudière-Appalaches.

Socio-Demographic Characteristics of Visible Minorities in RTS de l'Abitibi-Témiscamingue - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de l'Abitibi-Témiscamingue.

Socio-Demographic Characteristics of Visible Minorities in RTS de l'Est-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de l'Est-de-l'Île-de-Montréal.

Socio-Demographic Characteristics of Visible Minorities in RTS de l'Estrie - CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de l'Estrie – CHU de Sherbrooke.

Socio-Demographic Characteristics of Visible Minorities in RTS de l'Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de l'Ouest-de-l'Île-de-Montréal.

Socio-Demographic Characteristics of Visible Minorities in RTS de l'Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de l'Outaouais.

Socio-Demographic Characteristics of Visible Minorities in RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de la Capitale-Nationale.

Socio-Demographic Characteristics of Visible Minorities in RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de la Mauricie-et-du-Centre-du-Québec.

Socio-Demographic Characteristics of Visible Minorities in RTS de la Montérégie-Centre - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de la Montérégie-Centre.

Socio-Demographic Characteristics of Visible Minorities in RTS de la Montérégie-Est - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de la Montérégie-Est.

Socio-Demographic Characteristics of Visible Minorities in RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de la Montérégie-Ouest.

Socio-Demographic Characteristics of Visible Minorities in RTS de Lanaudière - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de Lanaudière.

Socio-Demographic Characteristics of Visible Minorities in RTS de Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de Laval.

Socio-Demographic Characteristics of Visible Minorities in RTS des Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS des Laurentides.

Socio-Demographic Characteristics of Visible Minorities in RTS du Bas-Saint-Laurent - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS du Bas-Saint-Laurent.

Socio-Demographic Characteristics of Visible Minorities in RTS du Centre-Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS du Centre-Ouest-de-l'Île-de-Montréal.

Socio-Demographic Characteristics of Visible Minorities in RTS du Centre-Sud-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS du Centre-Sud-de-l'Île-de-Montréal.

Socio-Demographic Characteristics of Visible Minorities in RTS du Nord-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS du Nord-de-l'Île-de-Montréal.

Socio-Demographic Characteristics of Visible Minorities in RTS du Saguenay-Lac-Saint-Jean - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS du Saguenay - Lac-Saint-Jean

Socio-Demographic Characteristics of Visible Minorities in Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Sherbrooke, which is considered a territory equivalent to an MRC.

Network News - Quebec Community Groups Network (QCGN) (2024)

Developing Regulations for Part VII (Advancement of Equality of Status and Use of English and French) of the Official Languages Act - Official Languages Centre of Excellence Office of the Chief Human Resources Officer (2024)

Quebec Community Groups Network: The Official Languages Act - Quebec Community Groups Network (QCGN) (2024)

Brief for Consultations with the Secrétariat aux relations avec les Québécois d’expression anglaise - Seniors Action Quebec (SAQ) (2024)

Portrait of the Clientele : Qualitative Research - Advisory Commitee for English-Speaking Quebecers (2024)

Official Languages in Canada - Canada. Office of the Commissioner of Official Languages (2024)

The English Presence in Quebec - Canada. Office of the Commissioner of Official Languages (2024)

Community Netlink - Community Health and Social Services Network (CHSSN) (2024)

Highlights of the Sociodemographic Profile of English-speaking Quebecers Aged 15-19 - Community Health and Social Services Network (CHSSN) (2024)

Nord-du-Québec - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Nord-du-Québec - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Québec - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Québec - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de Chaudière-Appalaches - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de Chaudière-Appalaches - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Abitibi-Témiscamingue - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Est-de-l'Île-de-Montréal - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Estrie – CHU de Sherbrooke - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Ouest-de-l'Île-de-Montréal - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Capitale-Nationale - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Capitale-Nationale - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Côte-Nord - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Côte-Nord - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Gaspésie - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Gaspésie - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Mauricie-et-du-Centre-du-Québec - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Mauricie-et-du-Centre-du-Québec - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Centre - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Centre - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Est - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Est - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de Lanaudière - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de Laval - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS des Îles - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS des Laurentides - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Bas-Saint-Laurent - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Centre-Ouest-de-l'Île-de-Montréal - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Centre-Sud-de-l'Île-de-Montréal - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Nord-de-l'Île-de-Montréal - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Saguenay – Lac-Saint-Jean - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

About the Réseau de l'Est de l'Île pour les Services en Anglais (REISA) Project - Community Health and Social Services Network (CHSSN); Réseau de l’est de l’île pour les services en anglais (REISA) (2024)

Annual Report 2023-2024 - Provincial Employment Roundtable (PERT) (2024)

Employment Profile of English Speakers in Capitale-Nationale - Provincial Employment Roundtable (PERT) (2024)
This report aims to contribute to the knowledge and understanding of the employment situation of Capitale-Nationale’s English-speaking communities, who are linguistic minorities in the region. It surveys the most current and comprehensive information on their demographic and labour force conditions. Topics covered include work activity, unemployment rate, income, and educational attainment of workers to provide a more holistic picture of English speakers’ employment and employability. In addition to examining the demographics and labour force of the region’s English-speaking population, this profile also examines the key characteristics of the labour market and industries in which English speakers work. The profile concludes with identifying some of the employment challenges and issues English-speaking workers in Capitale-Nationale face, as well as preliminary recommendations to help improve their labour market outcomes.

Employment Profile of English Speakers in Chaudière-Appalaches - Provincial Employment Roundtable (PERT) (2024)
This report aims to contribute to the knowledge and understanding of the employment situation of Chaudière-Appalaches’ English-speaking communities, who are linguistic minorities in the region. It surveys the most current and comprehensive information on their demographic and labour force conditions. Topics covered include work activity, unemployment rate, income, and educational attainment of workers to provide a more holistic picture of English speakers’ employment and employability. In addition to examining the demographics and labour force of the region’s English-speaking population, this profile also examines the key characteristics of the labour market and industries in which English speakers work. The profile concludes with identifying some of the employment challenges and issues for English-speaking workers in Chaudière-Appalaches, as well as preliminary recommendations to help improve their labour market outcomes.

Employment Profile of English Speakers in Côte-Nord - Provincial Employment Roundtable (PERT) (2024)
This report aims to contribute to the knowledge and understanding of the employment situation of Côte-Nord’s English-speaking communities, who are linguistic minorities in the region. It surveys the most current and comprehensive information on their demographic and labour force conditions. Topics covered include work activity, unemployment rate, income, and educational attainment of workers to provide a more holistic picture of English speakers’ employment and employability. In addition to examining the demographics and labour force of the region’s English-speaking population, this profile also examines the key characteristics of the labour market and industries in which English speakers work. The profile concludes with identifying some of the employment challenges and issues for English-speaking workers in Côte-Nord, as well as preliminary recommendations to help improve their labour market outcomes.

Employment Profile of English Speakers in Gaspésie–Îles-de-la-Madeleine - Provincial Employment Roundtable (PERT) (2024)
This report aims to contribute to the knowledge and understanding of the employment situation of Gaspésie-Îles-de-la-Madeleine’s English-speaking communities, who are linguistic minorities in the region. It surveys the most current and comprehensive information on their demographic and labour force conditions. Topics covered include work activity, unemployment rate, income, and educational attainment of workers to provide a more holistic picture of English speakers’ employment and employability. In addition to examining the demographics and labour force of the region’s English-speaking population, this profile also examines the key characteristics of the labour market and industries in which English speakers work. The profile concludes with identifying some of the employment challenges and issues for English-speaking workers in Gaspésie-Îles-de-la-Madeleine, as well as preliminary recommendations to help improve their labour market outcomes.

Employment Profile of English Speakers in Montérégie - Provincial Employment Roundtable (PERT) (2024)
This report aims to contribute to the knowledge and understanding of the employment situation of Montérégie’s English-speaking communities, who are linguistic minorities in the region. It surveys the most current and comprehensive information on their demographic and labour force conditions. Topics covered include work activity, unemployment rate, income, and educational attainment of workers to provide a more holistic picture of English speakers’ employment and employability. In addition to examining the demographics and labour force of the region’s English-speaking population, this profile also examines the key characteristics of the labour market and industries in which English speakers work. The profile concludes with identifying some of the employment challenges and issues for English-speaking workers in Montérégie, as well as preliminary recommendations to help improve their labour market outcomes.

Employment Profile of English Speakers in Saguenay–Lac-Saint-Jean - Provincial Employment Roundtable (PERT) (2024)
This report aims to contribute to the knowledge and understanding of the employment situation of Saguenay-Lac-Saint-Jean’s English-speaking communities, who are linguistic minorities in the region. It surveys the most current and comprehensive information on their demographic and labour force conditions. Topics covered include work activity, unemployment rate, income, and educational attainment of workers to provide a more holistic picture of English speakers’ employment and employability. In addition to examining the demographics and labour force of the region’s English-speaking population, this profile also examines the key characteristics of the labour market and industries in which English speakers work. The profile concludes by identifying some of the employment challenges and issues for English-speaking workers in Saguenay-Lac-Saint-Jean, as well as preliminary recommendations to help improve their labour market outcomes.

Employment Profile of English Speakers in the Laurentides - Provincial Employment Roundtable (PERT) (2024)
This report aims to contribute to the knowledge and understanding of the employment situation of Les Laurentides’ English-speaking communities, who are linguistic minorities in the region. It surveys the most current and comprehensive information on their demographic and labour force conditions. Topics covered include work activity, unemployment rate, income, and educational attainment of workers to provide a more holistic picture of English speakers’ employment and employability. In addition to examining the demographics and labour force of the region’s English-speaking population, this profile also examines the key characteristics of the labour market and industries in which English speakers work. The profile concludes with identifying some of the employment challenges and issues for English-speaking workers in Les Laurentides, as well as preliminary recommendations to help improve their labour market outcomes.

Employment Situation of English Speakers in Québec - Provincial Employment Roundtable (PERT) (2024)

Pre-Budget Submission 2024-2025 - Provincial Employment Roundtable (PERT) (2024)
The Provincial Employment Roundtable Table (PERT) is pleased to submit this brief and proposition to the Ministry of Finance’s 2024-25 Pre-budget consultations. Founded in 2020, PERT is a non-profit organization focused on addressing the employment and employability issues that are being faced by Québec’s English-speaking communities. Since its creation, PERT has become the leading voice on the solutions to English speakers’ employment challenges. Through its research and stakeholder coordination work, PERT has published over 25 reports that capture the employment issues and needs of English speakers across all 17 regions of the province and has established a membership of 90 employment service deliverers, educational institutions, regional organizations, and employers. The employment situation of Québec’s English-speaking population continues to worsen, as demonstrated by the higher unemployment rates and French-language barriers that English speakers face in Québec’s labour market. In this brief, we identify two key contributors to the continued employment challenges of English speakers: a lack of targeted employment services and programs for English speakers and a lack of work-integrated French language training programs to help them enter and remain in the labour market. English speakers’ employment and economic challenges are part of the larger economic headwinds that are facing Québec, which include unprecedented labour shortages, demographic decline, and problems with attracting and retaining talent. This mémoire summarizes PERT’s research findings, particularly the employment challenges facing the English-speaking community in Québec, and advances recommendations for the next budget that will address these challenges and help create a more productive, inclusive, and prosperous Québec for all.

Educational Experiences and Outcomes of Black Youth in Quebec English-Language High Schools - Quebec English-speaking Communities Research Network (QUESCREN) (2024)

Inclusive Mentorship Initiative - Townshippers' Association (2024)
This report provides an overview and evaluation of the 2023-2024 fiscal year ofTownshippers’ Association’s Inclusive Mentorship Initiative (IMI) funded by theSecrétariat aux relations avec les Québécois d’expression anglaise from December 2021to the present.
Keywords: Official Language Minority Community (OLMC)

Inclusive Mentorship Initiative - Townshippers' Association (2024)
This report provides an overview and evaluation of the 2023-2024 fiscal year ofTownshippers’ Association’s Inclusive Mentorship Initiative (IMI) funded by the Secrétariat aux relations avec les Québécois d’expression anglaise from December 2021 to the present. Founded in 1979, Townshippers’ Association is mandated to promote the interests ofthe ESC in the historical Eastern Townships, strengthening the cultural identity of thiscommunity, and encouraging the full participation of the English-speaking population in the community at large. Townshippers’ Association’s projects address heritage andculture, community development, access to health and social services, support for seniors, and youth retention. The Secretariat aux relations avec les Québécois d’expression anglaise is responsible forensuring that the concerns of English-speaking Quebecers are taken into account ingovernment orientations and decisions in collaboration with government ministries and bodies.

Exploring the English-speaking Landscape : A Typology of Vulnerability Associated with Employment in Quebec's English-speaking Population - Warnke, Jan; Bolger, Laura-Lee (Quebec English-Speaking Communities Research Network (QUESCREN), 2024)
This exploratory study uses geodemographic analytical methods to investigate the English-speaking population of Quebec, with a specific focus on vulnerability indicators associated with employment and their spatial distribution within the province. Using Ward’s cluster analysis method, eight distinct groups were identified and mapped, each showcasing unique characteristics that warrant tailored policy measures to effectively tackle regional employment challenges. Future research should delve into the differential impacts of various variables across clusters, particularly those related to mobility and aboriginal identity, thereby facilitating the derivation of targeted policy interventions.